Automated algorithm for reconstruction of the complete spine from multistation 7T MR data. Issue 6 (20th July 2012) - Dzyubachyk, Oleh; Lelieveldt, Boudewijn P. F.; Blaas, Jorik; Reijnierse, Monique; Webb, Andrew; van der Geest, Rob J.
Abstract: Recent technical developments in high‐field MRI have enabled high‐resolution imaging of the whole spine within clinically acceptable times. However, analysis of such data requires intensity inhomogeneity correction and volume stitching, both of which are typically performed manually. In this work, an automated method for reconstruction of the complete spine from multistation 7T MR data is presented. The method consists of a number of image processing steps, in particular intensity inhomogeneity correction and image registration for recovery of unknown interscan bed translations, which result in high‐quality spine volume reconstructions. The registration performance of the developed algorithm was validated on 18 datasets acquired in two or three stations. In all the test cases, our algorithm was able to produce correct reconstruction of the spine volume. The resulting mean registration error (0.53 mm) is found to be lower than the pixel size, demonstrating robustness and accuracy of the proposed method. Magn Reson Med, 2013. © 2012 Wiley Periodicals, Inc.